Development and Validation of an Improved HPLC-MS/MS Method for Quantifying Total and Unbound Lenalidomide in Human Plasma - Suhyun Lee; Seungwon Yang; Wang-Seob Shim; Eunseo Song; Seunghoon Han; Sung-Soo Park; Suein Choi; Sung Hwan Joo; Seok Jun Park; Beomjin Shin; Donghyun Kim; Hyeonsu Kim; et al. (MDPI AG, 2024)
Background/Objectives: This study aimed to develop a fully validated HPLC-MS/MS method for quantifying total and unbound lenalidomide concentrations in human plasma. Methods: Unbound concentrations were measured using plasma ultrafiltrate prepared with Amicon® Centrifugal Filters. Lenalidomide and lenalidomide-d5 (internal standard) were extracted from 50 μL of human plasma using liquid-liquid extraction. Chromatography was conducted with a Halo® C18 column using 0.1% formic acid and methanol (20:80, v/v) as the mobile phase. The mass spectrometer was operated in a positive ion mode with an electrospray ionization interface and multiple reaction monitoring modes. Results: Calibration curves were linear over the range of 5 to 1000 ng/mL (r2 > 0.996) for both the total and unbound lenalidomide. For total lenalidomide concentrations, between-run precision (coefficients of variation) and accuracy were 1.70-7.65% and 94.45-101.10%, respectively. For unbound concentrations, inter-day precision and accuracy were 1.98-10.55% and 93.95-98.48%, respectively. Conclusions: We developed a highly reproducible, sensitive, and efficient bioanalytical method using a smaller volume of plasma sample (50 μL) with a relatively short run time (2.5 min). The proposed analytical method was successfully applied to measure total and unbound lenalidomide concentrations at various time points in multiple myeloma patients with renal impairment.